RELATIONSHIP BETWEEN LOWER URINARY TRACT SYMPTOMS AND TREATMENT-RELATED BEHAVIOR IN HAZARA DIVISION - Muhammad Shahzad; Nasir Jamil, Muhammad; Faheem ul Haq; Aminullah; Ehsan Ul Islam; Muhammad Faridullah Thaimur (Journal of Ayub Medical College Abbottabad, 2024)
Background: Lower urinary tract symptoms (LUTS) adversely affect the quality of life and are usually under-reported because of a stigma associated with these symptoms. Unless specifically probed for these symptoms, most patients do not report Lower urinary tract symptoms. This study focused on the treatment seeking behavior of otherwise healthy individuals who had LUTS. The study aimed to determine the relationship between lower urinary tract symptoms and treatment-related behaviours among adults in the Hazara Division. Methods: This was a descriptive cross-sectional, questionnaire-based study of healthy attendants of patients admitted at a private medical center for any reason who were enrolled in this study and were interviewed using a simple questionnaire after obtaining informed consent. The patients were administered validated tools such as OAB-8 and IPSS. Results: Overall, 23.5% of study participants reported LUTS. Among the 968 study participants, 530 reported having LUTS less than half the time and 438 reported LUTS more than half the time during the past 3 months. Over 23.5% of patients sought any type of treatment for their symptoms. the likelihood of seeking medical attention was more in males experiencing issues such as urgency with distress (aOR 2.21 (1.11-4.05) CI 95%), frequency with distress (aOR 1.88 (1.01-4.21) 95%CI), slow urinary stream with distress (aOR 2.33 (1.13-4.49) CI 95%), hesitation (aOR 1.81 (1.02-2.15) CI 95%), and feeling of incomplete bladder emptying (aOR 3.13 (1.38-4.95) CI 95%). Similarly, females with symptoms like urgency with a fear of urine leak (aOR 5.33 (1.67-10.93) CI 95%), frequency (aOR 4.88 (1.29-9.94) CI 95%), urgency with distress (aOR 6.11 (2.33-13.20) CI 95%), and intermittency (aOR 2.32 (1.33-3.78) 95% CI), were more prone to seeking medical help. Conclusion: There is marked under-utilization of treatment for LUTS. Physicians need to adopt a proactive approach to identifying these symptoms and offering treatment.